Hard carbon material prepared from atmosphere-modulated hard carbon closed pore and pseudo graphite domain as well as preparation method and application of hard carbon material
By modulating its closed-cell and pseudographite domain structure in hard carbon materials, the problem of insufficient coordination of hard carbon materials in the prior art is solved, and high platform capacity and excellent sodium storage performance are achieved.
Patent Information
- Application Number
- CN202411785889.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The prior art is difficult to effectively coordinate the closed-cell and pseudographite domain structure in hard carbon materials, resulting in insufficient platform capacity and energy density of sodium ion batteries.
By using walnut shells as raw materials, high-temperature treatment with argon atmosphere or air preoxidation combined with an argon atmosphere or a hydrogen-containing mixture, the closed-cell and pseudographite domain structure of the hard carbon material is prepared. The method includes preoxidation or pre-carbonization treatment followed by argon or hydrogen-argon mixture at high temperatures to form abundant pseudographite domains and closed pores.
The platform capacity and first-time Coulomb efficiency of hard carbon materials have been significantly improved, achieving excellent sodium storage performance and high energy density.
Smart Images

Figure CN119528116A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage materials, and in particular relates to a hard carbon material prepared by atmosphere modulating hard carbon closed pores and pseudographite domains, and a preparation method and application thereof. Background Art
[0002] Due to the rapid consumption of fossil fuels, serious global climate issues, and the growing demand for electric or hybrid vehicles, there is an increasing demand for grid-scale energy storage systems with higher power / energy density and operability under extreme conditions. Lithium-ion batteries have been widely used in electronic devices and new energy vehicles due to their high energy density and cycle stability. However, due to the scarcity (0.0017 wt.%) and uneven distribution of lithium resources, the widespread application of lithium-ion batteries in large-scale energy storage systems faces major obstacles. Therefore, the development of new secondary batteries with high cost-effectiveness, high performance, and resource conservation is an inevitable trend. Sodium resources are abundant (2.3 wt.%) and low in price, making them an ideal alternative to lithium-ion batteries. Since the radius of sodium ions is much larger than that of lithium ions, and the interlayer spacing of graphite (0.335 nm) is smaller than that of Na + The interlayer spacing required for storage (0.370 nm) is too small, so graphite cannot store sodium ions well as the negative electrode of lithium-ion batteries. It is imperative to develop a negative electrode suitable for storing sodium ions.
[0003] Hard carbon is composed of curved graphene domains and numerous nanoscale pores and is considered to be the preferred negative electrode material for sodium-ion batteries. The twisted structure enhances the repulsion and interaction between carbon nanosheets, resulting in a larger interlayer spacing (0.3-0.42nm), which can be beneficial to Na + The interlayer spacing formed by pseudographite domains is between 0.37 and 0.40 nm, which is most suitable for sodium storage. Therefore, regulating the interlayer spacing of hard carbon and the pseudographite domain structure is the key to achieving high-capacity sodium storage.
[0004] The charge and discharge curve of hard carbon sodium storage shows a slope region (>0.1 V) and a platform region (<0.1 V), which correspond to the adsorption of sodium ions at defects, interlayer embedding and closed pore filling, respectively. However, improving the platform capacity of negative electrode materials is the key to improving the energy density of sodium ion batteries. High platform capacity requires the coordination of pseudographite domains and nanoscale closed pores. Lower or higher carbonization temperatures will affect the formation of pseudographite domains. Lower temperatures will cause excessive disorder of hard carbon, resulting in too many defects and irreversible adsorption of sodium ions, while higher temperatures will increase the degree of graphitization and reduce the interlayer spacing, which cannot better achieve the effective storage of sodium ions and thus lead to a decrease in platform capacity. Among them, the literature "Regulating oxygen functionalities of cellulose derived hard carbon toward superior sodium storage (J. Mater. Chem. A, 2024, 12, 5834.)" regulates the formation of pseudographite domains. The researchers cleave cellulose glycosidic bonds at different pre-oxidation temperatures to induce molecular chain crosslinking. The oxidative cross-linking process of cellulose produces more C=O and retains some CO. During the pyrolysis process, the graphite microcrystalline structure becomes thinner and longer, forming larger closed pores. Relevant literature shows that pre-oxidation can introduce more C=O, which hinders the formation of graphitization during high-temperature carbonization. There is also a document "A porous biomass-derived anode for high-performance sodium-ion batteries (Carbon, 2018, 129, 695-701.)" that shows that some oxygen defects can be removed by reduction treatment to improve the first coulombic efficiency of hard carbon negative electrode materials. However, there are still great challenges in the coordination of closed pores and pseudographite domains.
[0005] Therefore, a simple, efficient and easily scalable method is urgently needed to synergistically prepare hard carbon anode materials rich in closed pores and pseudographitic domains. Summary of the invention
[0006] In order to solve the existing problems, the purpose of the present invention is to provide a hard carbon material prepared by atmosphere modulating hard carbon closed pores and pseudographitic domains, and its preparation method and application. The present invention uses biomass walnut shells as raw materials, and adopts argon atmosphere or air pre-oxidation combined with high-temperature treatment of argon atmosphere or hydrogen-containing mixed gas to modulate hard carbon closed pores and pseudographitic domain structures. In the first stage, the CC bonds are cut by pre-carbonization in argon atmosphere, effectively destroying the long side chains on the single aromatic ring of lignin; or air pre-oxidation introduces oxygen elements to promote the formation of COC bonds and oxygen-containing covalent bonds, and promotes cross-linking during thermal decomposition to form a three-dimensional network structure; in the second stage, in the high-temperature process, the formation of closed pores is promoted by argon atmosphere or the reduction of hydrogen-containing mixed gas is conducive to the removal of oxygen-containing covalent bonds and dangling bonds, thereby effectively modulating the pseudographitic domains and closed pores of hard carbon. The platform capacity and the first coulomb efficiency are significantly improved, thereby achieving excellent sodium storage performance.
[0007] A method for preparing a hard carbon material prepared by atmosphere modulation of hard carbon closed pores and pseudo-graphite domains comprises the following steps: (1) Weigh walnut shells, wash them with deionized water, and then place them in a forced air drying oven for drying; (2) placing the dried walnut shells in a crusher for crushing and sieving; (3) washing the sieved walnut shell powder with hydrochloric acid to remove impurities and inorganic components in the walnut shell, then washing with deionized water until neutral, and drying in a forced air drying oven; (4) placing the acid-washed walnut shell powder in a muffle furnace for pre-oxidation or in a tube furnace for pre-carbonization, and taking it out after cooling to room temperature to obtain a pre-oxidized material or a pre-carbonized material; (5) The pre-oxidized material or pre-carbonized material obtained in step (4) is placed in a high-temperature tube furnace for high-temperature reaction, and taken out after cooling to room temperature to obtain a hard carbon material.
[0008] Preferably, the particle size of the walnut shell powder after sieving in step (2) is about 40-75 µm, so as to ensure that the prepared hard carbon negative electrode material rich in pseudographite domains has excellent sodium storage performance and high tap density.
[0009] Preferably, the hydrochloric acid in step (3) is 0.5-2 mol / L, more preferably 1 mol / L, to ensure that the appropriate hydrochloric acid concentration can remove inorganic salts and other impurities.
[0010] Preferably, the pre-carbonization or pre-oxidation temperature in step (4) is 200-400°C, more preferably 300°C, the time is 1-3 h, and the heating rate is 5°C / min.
[0011] Preferably, in step (4), when the pre-oxidation is carried out in a muffle furnace, the pre-oxidation atmosphere is air; and when the pre-carbonization is carried out in a tubular furnace, the pre-carbonization atmosphere is argon.
[0012] Preferably, the high temperature reaction temperature in step (5) is 1200-1500°C, more preferably 1400°C, the reaction time is 1-3 h, and the heating rate is 3°C / min.
[0013] Preferably, in step (5), the atmosphere in which the pre-oxidized material obtained in step (4) is subjected to a high-temperature reaction is argon; and the atmosphere in which the pre-carbonized material obtained in step (4) is subjected to a high-temperature reaction is a hydrogen-containing mixed gas. More preferably, the concentration of the hydrogen-containing mixed gas is 5%-10%.
[0014] The present invention also provides application of the hard carbon material in sodium ion batteries.
[0015] Beneficial Effects (1) The raw material used in the present invention is walnut shell, which has low cost, simple method and easy scale-up.
[0016] (2) The present invention modulates the closed pores and pseudographite domains of hard carbon by changing the atmosphere, wherein argon atmosphere pre-carbonization or air pre-oxidation shears the C-C bonds at a certain temperature. Pre-oxidation can also introduce oxygen elements to form oxygen-containing covalent bonds such as C-O-C bonds, thereby promoting the formation of a three-dimensional network of stable structures during pyrolysis. More pseudographite domains and closed nanopores are formed at high temperatures through argon atmosphere or hydrogen mixed gas atmosphere.
[0017] (3) The pseudographite domains modulated by the present invention have good electrical conductivity and fast ion transport properties by changing the atmosphere; the modulated rich closed-pore structure is conducive to achieving a high platform sodium storage capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 TEM image of the hard carbon prepared in Example 1 of the present invention; Figure 2 XRD diagram of the hard carbon prepared in Examples 1-3 of the present invention; Figure 3 The second cycle charge-discharge curve of the hard carbon prepared in Example 1-3 of the present invention; Figure 4 The rate performance diagram of the hard carbon prepared in Examples 1-3 of the present invention; Figure 5 XRD patterns of the hard carbons prepared in Example 1 and Examples 4-8 of the present invention; Figure 6 The second cycle charge-discharge curve diagram of the hard carbon prepared in Example 1 and Examples 4-8 of the present invention; Figure 7 This is a rate performance diagram of the hard carbon prepared in Example 1 and Examples 4-8 of the present invention. DETAILED DESCRIPTION
[0019] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, the embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.
[0020] Example 1 A method for preparing hard carbon material prepared by atmosphere modulation of hard carbon closed pores and pseudo-graphite domains (1) Weigh 500 g of walnut shells and wash them in deionized water. After washing, place them in a forced air drying oven for drying.
[0021] (2) Weigh 200 g of walnut shells washed with deionized water and dried, crush them, and sieve them through a 200-mesh sieve with a particle size of less than 74 µm to ensure better pre-oxidation and promote the destruction of CC bonds and the formation of oxygen-containing covalent bonds during the pyrolysis process.
[0022] (3) Weigh 5 g of sieved walnut shell powder and place it in 1 mol / L hydrochloric acid and stir for 12 h. Wash it with deionized water until it is neutral and dry it in a forced air drying oven at 60 °C. Sufficient stirring time ensures that the hydrochloric acid can fully remove the inorganic salts and other impurities in the walnut shell.
[0023] (4) The acid-washed walnut shell powder was placed in a muffle furnace for pre-oxidation treatment at a temperature of 300 °C for 2 h at a heating rate of 5 °C / min. After cooling to room temperature, the powder was taken out to obtain a pre-oxidized material. The purpose of pre-oxidation at 300 °C for 2 h was to ensure the decomposition of cellulose and hemicellulose and effectively destroy the long side chains on the single aromatic ring of lignin, thereby promoting the cross-linking of C and O atoms during the thermal decomposition process to form a three-dimensional network structure.
[0024] (5) The pre-oxidized material obtained in step (4) is placed in a high-temperature tubular furnace, and reduced at 1400°C for 2 h in a hydrogen-argon mixed gas atmosphere at a heating rate of 3°C / min. After cooling to room temperature, the pre-oxidized material is taken out to obtain a hard carbon material having abundant pseudographitic domains and a closed-pore structure. In the high-temperature process, the hydrogen-argon mixed atmosphere is used to regulate the oxygen content and remove some oxygen defects, which is conducive to the formation of more pseudographitic domains and closed pores. The pseudographitic domains provide a suitable interlayer spacing for the rapid transmission of sodium ions, and the abundant closed pores provide more sites for the storage of sodium ions.
[0025] (6) Preparation of electrode sheets: The prepared pseudographite domain-rich hard carbon material, acetylene black, and binder PVDF were weighed in a mass ratio of 8:1:1 and mixed evenly in a mortar. An appropriate amount of N-methylpyrrolidone (NMP) solvent was added and stirred evenly to obtain a slurry, which was then coated on a copper (Cu) foil. The slurry was dried in a vacuum drying oven at 120 °C for 12 h and cut into 12 mm round negative electrode sheets for later use.
[0026] (7) The button cell is assembled in a glove box filled with inert gas. The hard carbon material electrode prepared in step (5) is used as the negative electrode, the commercial electrolyte 1M NaPF6DIGLYME=100 Vol% is used as the electrolyte, and the metal Na sheet is used as the counter electrode to assemble the button cell.
[0027] (8) The assembled 2025 button battery was charged and discharged on a constant current test system with a voltage range of 0-2 V.
[0028] Figure 1 This is a TEM image of the hard carbon prepared in Example 1 of the present invention; as can be seen from the figure, it can be clearly seen that there are abundant pseudographite microcrystalline structures and abundant closed-pore structures, which are beneficial to improving the sodium storage capacity of the platform area.
[0029] The hard carbon anode material prepared under the above conditions has a current density of 354.5 mAh g at 25 mA / g. -1 reversible capacity.
[0030] Example 2 A method for preparing hard carbon material prepared by atmosphere modulation of hard carbon closed pores and pseudo-graphite domains (1) Weigh 500 g of walnut shells and wash them in deionized water. After washing, place them in a forced air drying oven for drying.
[0031] (2) Weigh 200 g of walnut shells washed with deionized water and dried, crush them, and sieve them through a 200-mesh sieve with a particle size of less than 74 µm to ensure better pre-oxidation and promote the destruction of CC bonds and the formation of oxygen-containing covalent bonds during the pyrolysis process.
[0032] (3) Weigh 5 g of sieved walnut shell powder and place it in 1 mol / L hydrochloric acid and stir for 12 h. Wash it with deionized water until it is neutral and dry it in a forced air drying oven at 60 °C. Sufficient stirring time ensures that the hydrochloric acid can fully remove the inorganic salts and other impurities in the walnut shell.
[0033] (4) The acid-washed walnut shell powder was placed in a muffle furnace for pre-oxidation treatment at a temperature of 300 °C, a pre-oxidation time of 1 h, and a heating rate of 5 °C / min. After the temperature was cooled to room temperature, the powder was taken out to obtain a pre-oxidized material.
[0034] (5) The pre-oxidized material obtained in step (4) is placed in a high-temperature tube furnace, and reduced at 1400°C for 2 h in a hydrogen-argon mixed gas atmosphere at a heating rate of 3°C / min. After cooling to room temperature, the material is taken out to obtain a hard carbon material. Since the oxidation time is short and the reduction time is long, the hard carbon forms more graphite-like domains, which is not conducive to the storage of sodium ions.
[0035] (6) Preparation of electrode sheets: The prepared pseudographite domain-rich hard carbon material, acetylene black, and binder PVDF were weighed in a mass ratio of 8:1:1 and mixed evenly in a mortar. An appropriate amount of N-methylpyrrolidone (NMP) solvent was added and stirred evenly to obtain a slurry, which was then coated on a copper (Cu) foil. The slurry was dried in a vacuum drying oven at 120 °C for 12 h and cut into 12 mm round negative electrode sheets for later use.
[0036] (7) The button cell is assembled in a glove box filled with inert gas. The hard carbon material electrode prepared in step (5) is used as the negative electrode, the commercial electrolyte 1M NaPF6DIGLYME=100 Vol% is used as the electrolyte, and the metal Na sheet is used as the counter electrode to assemble the button cell.
[0037] (8) The assembled 2025 button battery was charged and discharged on a constant current test system with a voltage range of 0-2 V.
[0038] The hard carbon anode material prepared under the above conditions has a high conductivity at 25 mA g -1 The current density is 306.2 mAhg -1 reversible capacity.
[0039] Example 3 A method for preparing hard carbon material prepared by atmosphere modulation of hard carbon closed pores and pseudo-graphite domains (1) Weigh 500 g of walnut shells and wash them in deionized water. After washing, place them in a forced air drying oven for drying.
[0040] (2) Weigh 200 g of walnut shells washed with deionized water and dried, crush them, and sieve them through a 200-mesh sieve with a particle size of less than 74 µm to ensure better pre-oxidation and promote the destruction of CC bonds and the formation of oxygen-containing covalent bonds during the pyrolysis process.
[0041] (3) Weigh 5 g of sieved walnut shell powder and place it in 1 mol / L hydrochloric acid and stir for 12 h. Wash it with deionized water until it is neutral and dry it in a forced air drying oven at 60 °C. Sufficient stirring time ensures that the hydrochloric acid can fully remove the inorganic salts and other impurities in the walnut shell.
[0042] (4) The acid-washed walnut shell powder was placed in a muffle furnace for pre-oxidation treatment at a temperature of 300 °C, a pre-oxidation time of 3 h, and a heating rate of 5 °C / min. After the temperature was cooled to room temperature, the powder was taken out to obtain a pre-oxidized material.
[0043] (5) The pre-oxidized material obtained in step (4) was placed in a high-temperature tube furnace, reduced at 1400°C for 2 h in a hydrogen-argon mixed gas atmosphere at a heating rate of 3°C / min, and taken out after cooling to room temperature to obtain a hard carbon material. However, due to the long oxidation time and insufficient reduction time, most of the amorphous carbon material of the hard carbon was not transformed into pseudographite domains.
[0044] (6) Preparation of electrode sheets: The prepared pseudographite domain-rich hard carbon material, acetylene black, and binder PVDF were weighed in a mass ratio of 8:1:1 and mixed evenly in a mortar. An appropriate amount of N-methylpyrrolidone (NMP) solvent was added and stirred evenly to obtain a slurry, which was then coated on a copper (Cu) foil. The slurry was dried in a vacuum drying oven at 120 °C for 12 h and cut into 12 mm round negative electrode sheets for later use.
[0045] (7) The button cell is assembled in a glove box filled with inert gas. The hard carbon material electrode prepared in step (5) is used as the negative electrode, the commercial electrolyte 1M NaPF6DIGLYME=100 Vol% is used as the electrolyte, and the metal Na sheet is used as the counter electrode to assemble the button cell.
[0046] (8) The assembled 2025 button battery was charged and discharged on a constant current test system with a voltage range of 0-2 V.
[0047] The hard carbon anode material prepared under the above conditions has a high conductivity at 25 mA g -1 The current density is 324.5 mAhg -1 reversible capacity.
[0048] Figure 2 The XRD diagram of Example 1-3 shows that after appropriate pre-oxidation treatment combined with argon-hydrogen mixed gas reduction, abundant pseudographite domains and closed-pore structures are obtained. When the pre-oxidation time is short, more graphite-like domains will be formed, which is not conducive to the storage of sodium ions. When the pre-oxidation time is too long, the amorphous carbon material cannot be converted into pseudographite domains.
[0049] Figure 3 The charge-discharge curve of the second cycle of Example 1-3 shows that after appropriate pre-oxidation treatment combined with argon-hydrogen mixed gas reduction, it has a higher platform capacity and specific capacity, and the platform area capacity is as high as 246.7 mAh g -1 .
[0050] Figure 4 The figure shows the rate performance of Examples 1-3. It can be seen from the figure that suitable pre-oxidation treatment can achieve excellent rate performance.
[0051] Example 4 A method for preparing hard carbon material prepared by atmosphere modulation of hard carbon closed pores and pseudo-graphite domains (1) Weigh 500 g of walnut shells and wash them in deionized water. After washing, place them in a forced air drying oven for drying.
[0052] (2) Weigh 200 g of walnut shells washed with deionized water and dried, crush them, and sieve them through a 200-mesh sieve with a particle size of less than 74 µm to ensure better pre-oxidation and promote the destruction of CC bonds and the formation of oxygen-containing covalent bonds during the pyrolysis process.
[0053] (3) Weigh 5 g of sieved walnut shell powder and place it in 1 mol / L hydrochloric acid and stir for 12 h. Wash it with deionized water until it is neutral and dry it in a forced air drying oven at 60 °C. Sufficient stirring time ensures that the hydrochloric acid can fully remove the inorganic salts and other impurities in the walnut shell.
[0054] (4) The acid-washed walnut shell powder was placed in a muffle furnace for pre-oxidation treatment at a temperature of 300°C for 2 h at a heating rate of 5°C / min. After cooling to room temperature, the powder was taken out to obtain a pre-oxidized material. The purpose of pre-oxidation at 300°C for 2 h was to ensure the decomposition of cellulose and hemicellulose and effectively destroy the long side chains on the single aromatic ring of lignin, promoting the cross-linking of C and O atoms during the thermal decomposition process to form a three-dimensional network structure.
[0055] (5) The pre-oxidized material obtained in step (4) is placed in a high-temperature tube furnace and reduced at 1400 °C for 2 h under an argon atmosphere at a heating rate of 3 °C / min. After cooling to room temperature, the material is taken out to obtain a hard carbon material. The most suitable system is verified to be an oxidation-first-reduction system. High temperature is conducive to the formation of closed pores, but the introduction of more oxygen-containing functional groups hinders the formation of pseudographite domains at high temperatures, so that the carbonized material has a large amount of amorphous structure.
[0056] (6) Preparation of electrode sheets: The prepared pseudographite domain-rich hard carbon material, acetylene black, and binder PVDF were weighed in a mass ratio of 8:1:1 and mixed evenly in a mortar. An appropriate amount of N-methylpyrrolidone (NMP) solvent was added and stirred evenly to obtain a slurry, which was then coated on a copper (Cu) foil. The slurry was dried in a vacuum drying oven at 120 °C for 12 h and cut into 12 mm round negative electrode sheets for later use.
[0057] (7) The button cell is assembled in a glove box filled with inert gas. The hard carbon material electrode prepared in step (5) is used as the negative electrode, the commercial electrolyte 1M NaPF6DIGLYME=100 Vol% is used as the electrolyte, and the metal Na sheet is used as the counter electrode to assemble the button cell.
[0058] (8) The assembled 2025 button battery was charged and discharged on a constant current test system with a voltage range of 0-2 V.
[0059] The hard carbon anode material prepared under the above conditions has a high conductivity at 25 mA g -1 The current density is 338.2 mAhg -1 reversible capacity.
[0060] Example 5 A method for preparing hard carbon material prepared by atmosphere modulation of hard carbon closed pores and pseudo-graphite domains (1) Weigh 500 g of walnut shells and wash them in deionized water. After washing, place them in a forced air drying oven for drying.
[0061] (2) Weigh 200 g of walnut shells that have been washed with deionized water and dried, crush them, and sieve them through a 200-mesh sieve, with the particle size being less than 74 µm.
[0062] (3) Weigh 5 g of sieved walnut shell powder and place it in 1 mol / L hydrochloric acid and stir for 12 h. Wash it with deionized water until it is neutral and dry it in a forced air drying oven at 60 °C. Sufficient stirring time ensures that the hydrochloric acid can fully remove the inorganic salts and other impurities in the walnut shell.
[0063] (4) The acid-washed walnut shell powder was placed in a tube furnace and pre-carbonized under an argon atmosphere at a temperature of 300 °C for 2 h at a heating rate of 5 °C / min. The powder was taken out after cooling to room temperature to obtain a pre-carbonized material.
[0064] (5) The pre-carbonized material obtained in step (4) is placed in a high-temperature tube furnace and subjected to a high-temperature reaction at 1400°C in an argon atmosphere for 2 h at a heating rate of 3°C / min. After cooling to room temperature, the pre-carbonized material is taken out to obtain a hard carbon material.
[0065] (6) Preparation of electrode sheets: The prepared pseudographite domain-rich hard carbon material, acetylene black, and binder PVDF were weighed in a mass ratio of 8:1:1 and mixed evenly in a mortar. An appropriate amount of N-methylpyrrolidone (NMP) solvent was added and stirred evenly to obtain a slurry, which was then coated on a copper (Cu) foil. The slurry was dried in a vacuum drying oven at 120 °C for 12 h and cut into 12 mm round negative electrode sheets for later use.
[0066] (7) The button cell is assembled in a glove box filled with inert gas. The hard carbon material electrode prepared in step (5) is used as the negative electrode, the commercial electrolyte 1M NaPF6DIGLYME=100 Vol% is used as the electrolyte, and the metal Na sheet is used as the counter electrode to assemble the button cell.
[0067] (8) The assembled 2025 button battery was charged and discharged on a constant current test system with a voltage range of 0-2 V.
[0068] In the present invention, since there is no intervention of hydrogen and oxygen under the conditions, the material after high-temperature carbonization has the most amorphous structure and fewer pseudographite domains.
[0069] The hard carbon anode material prepared under the above conditions has a high conductivity at 25 mA g -1 The current density is 326.8 mAhg -1 reversible capacity.
[0070] Example 6 A method for preparing hard carbon material prepared by atmosphere modulation of hard carbon closed pores and pseudo-graphite domains (1) Weigh 500 g of walnut shells and wash them in deionized water. After washing, place them in a forced air drying oven for drying.
[0071] (2) Weigh 200 g of walnut shells that have been washed with deionized water and dried, crush them, and sieve them through a 200-mesh sieve, with the particle size being less than 74 µm.
[0072] (3) Weigh 5 g of sieved walnut shell powder and place it in 1 mol / L hydrochloric acid and stir for 12 h. Wash it with deionized water until it is neutral and dry it in a forced air drying oven at 60 °C. Sufficient stirring time ensures that the hydrochloric acid can fully remove the inorganic salts and other impurities in the walnut shell.
[0073] (4) The acid-washed walnut shell powder was placed in a tube furnace and pre-carbonized under an argon atmosphere at a temperature of 300 °C for 2 h at a heating rate of 5 °C / min. The powder was taken out after cooling to room temperature to obtain a pre-carbonized material.
[0074] (5) The pre-carbonized material obtained in step (4) is placed in a high-temperature tube furnace and reduced at 1400°C in a hydrogen-argon mixed gas atmosphere for 2 h at a heating rate of 3°C / min. After cooling to room temperature, the pre-carbonized material is taken out to obtain a hard carbon material.
[0075] (6) Preparation of electrode sheets: The prepared pseudographite domain-rich hard carbon material, acetylene black, and binder PVDF were weighed in a mass ratio of 8:1:1 and mixed evenly in a mortar. An appropriate amount of N-methylpyrrolidone (NMP) solvent was added and stirred evenly to obtain a slurry, which was then coated on a copper (Cu) foil. The slurry was dried in a vacuum drying oven at 120 °C for 12 h and cut into 12 mm round negative electrode sheets for later use.
[0076] (7) The button cell is assembled in a glove box filled with inert gas. The hard carbon material electrode prepared in step (5) is used as the negative electrode, the commercial electrolyte 1M NaPF6DIGLYME=100 Vol% is used as the electrolyte, and the metal Na sheet is used as the counter electrode to assemble the button cell.
[0077] (8) The assembled 2025 button battery was charged and discharged on a constant current test system with a voltage range of 0-2 V.
[0078] In the present invention, since only hydrogen reduction is performed under the conditions and no oxygen is introduced, excessive removal of high-temperature carbonized oxygen is caused. Therefore, the material after high-temperature carbonization exhibits more graphite-like domains, which is not conducive to the storage of sodium ions.
[0079] The hard carbon anode material prepared under the above conditions has a high conductivity at 25 mA g -1 The current density is 327.9 mAhg -1 reversible capacity.
[0080] Example 7 A method for preparing hard carbon material prepared by atmosphere modulation of hard carbon closed pores and pseudo-graphite domains (1) Weigh 500 g of walnut shells and wash them in deionized water. After washing, place them in a forced air drying oven for drying.
[0081] (2) Weigh 200 g of walnut shells that have been washed with deionized water and dried, crush them, and sieve them through a 200-mesh sieve, with the particle size being less than 74 µm.
[0082] (3) Weigh 5 g of sieved walnut shell powder and place it in 1 mol / L hydrochloric acid and stir for 12 h. Wash it with deionized water until it is neutral and dry it in a forced air drying oven at 60 °C. Sufficient stirring time ensures that the hydrochloric acid can fully remove the inorganic salts and other impurities in the walnut shell.
[0083] (4) The acid-washed walnut shell powder was placed in a tubular furnace and pre-carbonized in a hydrogen atmosphere at a temperature of 300 °C for 2 h at a heating rate of 5 °C / min. The powder was taken out after cooling to room temperature to obtain a pre-carbonized material.
[0084] (5) The pre-carbonized material obtained in step (4) is placed in a high-temperature tube furnace and reduced at 1400°C in an argon atmosphere for 2 h at a heating rate of 3°C / min. After cooling to room temperature, the pre-carbonized material is taken out to obtain a hard carbon material.
[0085] (6) Preparation of electrode sheets: The prepared pseudographite domain-rich hard carbon material, acetylene black, and binder PVDF were weighed in a mass ratio of 8:1:1 and mixed evenly in a mortar. An appropriate amount of N-methylpyrrolidone (NMP) solvent was added and stirred evenly to obtain a slurry, which was then coated on a copper (Cu) foil. The slurry was dried in a vacuum drying oven at 120 °C for 12 h and cut into 12 mm round negative electrode sheets for later use.
[0086] (7) The button cell is assembled in a glove box filled with inert gas. The hard carbon material electrode prepared in step (5) is used as the negative electrode, the commercial electrolyte 1M NaPF6DIGLYME=100 Vol% is used as the electrolyte, and the metal Na sheet is used as the counter electrode to assemble the button cell.
[0087] (8) The assembled 2025 button battery was charged and discharged on a constant current test system with a voltage range of 0-2 V.
[0088] In the present invention, since a small amount of oxygen is removed by low-temperature hydrogen reduction under such conditions, the carbon atoms cannot be connected, so that the carbon material after high-temperature treatment exhibits more amorphous structures.
[0089] The hard carbon anode material prepared under the above conditions has a current density of 321.6 mAhg at 25 mA / g. -1 reversible capacity.
[0090] Example 8 A method for preparing hard carbon material prepared by atmosphere modulation of hard carbon closed pores and pseudo-graphite domains (1) Weigh 500 g of walnut shells and wash them in deionized water. After washing, place them in a forced air drying oven for drying.
[0091] (2) Weigh 200 g of walnut shells that have been washed with deionized water and dried, crush them, and sieve them through a 200-mesh sieve, with the particle size being less than 74 µm.
[0092] (3) Weigh 5 g of sieved walnut shell powder and place it in 1 mol / L hydrochloric acid and stir for 12 h. Wash it with deionized water until it is neutral and dry it in a forced air drying oven at 60 °C. Sufficient stirring time ensures that the hydrochloric acid can fully remove the inorganic salts and other impurities in the walnut shell.
[0093] (4) The acid-washed walnut shell powder was placed in a tubular furnace and pre-carbonized in a hydrogen-argon mixed gas atmosphere at a temperature of 300 °C for 2 h at a heating rate of 5 °C / min. The powder was taken out after cooling to room temperature to obtain a pre-carbonized material.
[0094] (5) The pre-carbonized material obtained in step (4) is placed in a high-temperature tube furnace and reduced at 1400°C in a hydrogen-argon mixed gas atmosphere for 2 h at a heating rate of 3°C / min. After cooling to room temperature, the pre-carbonized material is taken out to obtain a hard carbon material.
[0095] (6) Preparation of electrode sheets: The prepared pseudographite domain-rich hard carbon material, acetylene black, and binder PVDF were weighed in a mass ratio of 8:1:1 and mixed evenly in a mortar. An appropriate amount of N-methylpyrrolidone (NMP) solvent was added and stirred evenly to obtain a slurry, which was then coated on a copper (Cu) foil. The slurry was dried in a vacuum drying oven at 120 °C for 12 h and cut into 12 mm round negative electrode sheets for later use.
[0096] (7) The button cell is assembled in a glove box filled with inert gas. The hard carbon material electrode prepared in step (5) is used as the negative electrode, the commercial electrolyte 1M NaPF6DIGLYME=100 Vol% is used as the electrolyte, and the metal Na sheet is used as the counter electrode to assemble the button cell.
[0097] (8) The assembled 2025 button battery was charged and discharged on a constant current test system with a voltage range of 0-2 V.
[0098] The present invention removes a small amount of oxygen by low-temperature hydrogen reduction under this condition, and continues to use hydrogen reduction during the high-temperature carbon atom rearrangement process to promote the formation of graphitization.
[0099] The hard carbon anode material prepared under the above conditions has a current density of 326.3 mAhg at 25 mA / g. -1 reversible capacity.
[0100] Figure 5 The XRD diagrams of pre-carbonization or pre-oxidation in different atmospheres and high-temperature treatment in different atmospheres show that the first stage of pre-oxidation or pre-carbonization cuts off the CC bond, effectively destroying the long side chain on the single aromatic ring of lignin; or air pre-oxidation introduces oxygen elements to promote the formation of COC bonds and oxygen-containing covalent bonds, promotes cross-linking during thermal decomposition to form a three-dimensional network structure, and further regulates the structure of pseudographite domains and closed pores. It was found that pre-oxidation and high-temperature hydrogen reduction are conducive to achieving a reasonable combination of pseudographite domains and closed pores.
[0101] Figure 6These are the second cycle charge and discharge curves of pre-carbonization or pre-oxidation in different atmospheres and high-temperature treatment in different atmospheres. It can be seen from the figure that pre-oxidation and high-temperature hydrogen reduction obtain the highest specific capacity and the longest platform capacity.
[0102] Figure 7 The figure shows the rate performance of pre-carbonization or pre-oxidation in different atmospheres and high-temperature treatment in different atmospheres. It can be seen from the figure that the best rate performance is achieved by the same pre-oxidation and high-temperature hydrogen reduction.
[0103] Through the analysis of the above embodiments, it can be seen that: when the oxidation time is long or short, it is not conducive to the formation of hard carbon closed pores; the structure of pseudographite domains and closed pores can be optimized by adjusting the treatment under different atmospheres.
[0104] The above content shows the basic principle, main features and advantages of the present invention. For those skilled in the art, it should be understood that the present invention is not limited to the specific description of the above embodiments. The above embodiments and the contents described in the specification only illustrate the principles of the present invention. Any changes and improvements without departing from the spirit and scope of the present invention should be regarded as part of the present invention and protected. Therefore, the protection scope of the present invention should be determined according to the attached claims and their equivalent forms.
Claims
1. A method for preparing a hard carbon material prepared by atmosphere modulation of hard carbon closed pores and pseudo-graphite domains, characterized in that: The following steps are involved: (1) Weigh walnut shells, wash them with deionized water, and then place them in a forced air drying oven for drying; (2) placing the dried walnut shells in a crusher for crushing and sieving; (3) washing the sieved walnut shell powder with hydrochloric acid, then washing with deionized water until neutral, and drying in a forced air drying oven; (4) placing the acid-washed walnut shell powder in a muffle furnace for pre-oxidation or in a tube furnace for pre-carbonization, and taking it out after cooling to room temperature to obtain a pre-oxidized material or a pre-carbonized material; (5) The pre-oxidized material or pre-carbonized material obtained in step (4) is placed in a high-temperature tube furnace for high-temperature reaction, and taken out after cooling to room temperature to obtain a hard carbon material.
2. The preparation method according to claim 1, characterized in that The particle size of the walnut shell powder after sieving in the step (2) is about 40-75 µm.
3. The preparation method according to claim 1, characterized in that The concentration of hydrochloric acid in step (3) is 0.5-2 mol / L.
4. The preparation method according to claim 3, characterized in that The concentration of hydrochloric acid in step (3) is 1 mol / L.
5. The preparation method according to claim 1, characterized in that The pre-carbonization or pre-oxidation temperature in step (4) is 200-400°C, preferably 300°C, the time is 1-3 h, and the heating rate is 5°C / min.
6. The preparation method according to claim 1, characterized in that: When the pre-oxidation is carried out in a muffle furnace in step (4), the pre-oxidation atmosphere is air; when the pre-carbonization is carried out in a tubular furnace, the pre-carbonization atmosphere is argon.
7. The preparation method according to claim 1, characterized in that In step (5), the high temperature reaction temperature is 1200-1500°C, preferably 1400°C, the reaction time is 1-3 h, and the heating rate is 3°C / min.
8. The preparation method according to claim 1, characterized in that: In the step (5), the atmosphere for the high-temperature reaction of the pre-oxidized material obtained in the step (4) is argon; the atmosphere for the high-temperature reaction of the pre-carbonized material obtained in the step (4) is a hydrogen-containing mixed gas, and preferably, the concentration of hydrogen in the hydrogen-containing mixed gas is 5%-10%.
9. The hard carbon material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the hard carbon material according to claim 9 in sodium ion batteries.
Citation Information
Patent Citations
A carbon-based negative electrode material with high ramp capacity and a preparation method and use thereof
CN109148884A
Sodium-ion battery carbon negative electrode material prepared based on waste wood chips and preparation method thereof
CN113651307A
Preparation method of high-first-effect nano blocky sodium ion battery negative electrode biomass hard carbon
CN118754099A
Preparation method of biomass hard carbon material, biomass hard carbon material and secondary battery
CN118929622A
Carbon-based anode material with high slopecapacity and preparation method therefor and use thereof
US20210253427A1
Cited By
Phosphorus-doped biomass-based hard carbon material, negative electrode, sodium ion battery and preparation method
CN121063515A